INVERSE NODAL PROBLEM FOR p-LAPLACIAN STRING EQUATION WITH PRUFER SUBSTITUTION - Yilmaz, Emrah; Gulsen, Tuba; Koyunbakan, Hikmet (Publ House Bulgarian Acad Sci, 2022)
We consider an inverse nodal problem for p-Laplacian string equation under some boundary conditions. Asymptotic formulas for eigenvalues and nodal parameters are constructed by modified Prufer substitution. The most important process is to apply modified Prufer substitution to get an exhaustive asymptotic estimate for eigenvalues. Moreover, a reconstruction formula for density function of p-Laplacian string equation is obtained by nodal parameters. Generated outcomes are the generalization of the known string problem.
Keywords: inverse nodal problem; Prufer substitution; p-Laplacian string equation